Clinical reasoning during dysphagia assessment and management in acute care: A longitudinal qualitative study. - Gunasekaran, Sulekha; Murray, Joanne; Doeltgen, Sebastian (International Journal of Language & Communication Disorders (John Wiley & Sons, Inc.), 2024)
Background: Competent clinical reasoning forms the foundation for effective and efficient clinical swallowing examination (CSE) and consequent dysphagia management decisions. While the nature of initial CSEs has been evaluated, it remains unclear how new information gathered by speech–language therapists (SLTs) throughout a patient's acute‐care journey is integrated into their initial clinical reasoning and management processes and used to review and revise initial management recommendations. Aims: To understand how SLTs' clinical reasoning and decision‐making regarding dysphagia assessment and management evolve as patients transition through acute hospital care from referral to discharge. Methods & Procedures: A longitudinal, qualitative approach was employed to gather information from two SLTs who managed six patients at a metropolitan acute‐care hospital. A retrospective 'think‐aloud' protocol was utilized to prompt SLTs regarding their clinical reasoning and decision‐making processes during initial and subsequent CSEs and patient interactions. Three types of concept maps were created based on these interviews: a descriptive concept map, a reasoning map and a hypothesis map. All concept maps were evaluated regarding their overall structure, facts gathered, types of reasoning engaged in (inductive versus deductive), types of hypotheses generated, and the diagnosis and management recommendations made following initial CSE and during subsequent dysphagia management. Outcomes & Results: Initial CSEs involved a rich process of fact‐gathering, that was predominantly led by inductive reasoning (hypothesis generation) and some application of deductive reasoning (hypothesis testing), with the primary aims of determining the presence of dysphagia and identifying the safest diet and fluid recommendations. During follow‐up assessments, SLTs engaged in increasingly more deductive testing of initial hypotheses, including fact‐gathering aimed at determining the tolerance of current diet and fluid recommendations or the suitability for diet and/or fluid upgrade and less inductive reasoning. Consistent with this aim, SLTs' hypotheses were focused primarily on airway protection and medical status during the follow‐up phase. Overall, both initial and follow‐up swallowing assessments were targeted primarily at identifying suitable management recommendations, and less so on identifying and formulating diagnoses. None of the patients presented with adverse respiratory and/or swallowing outcomes during admission and following discharge from speech pathology. Conclusions & Implications: Swallowing assessment and management across the acute‐care journey was observed as a high‐quality, patient‐centred process characterized by iterative cycles of inductive and deductive reasoning. This approach appears to maximize efficiency without compromising the quality of care. The outcomes of this research encourage further investigation and translation to tertiary and post‐professional education contexts as a clear understanding of the processes involved in reaching diagnoses and management recommendations can inform career‐long refinement of clinical skills. WHAT THIS PAPER ADDS: What is already known on the subject: SLTs' clinical reasoning processes during initial CSE employ iterative cycles of inductive and deductive reasoning, reflecting a patient‐centred assessment process. To date it is unknown how SLTs engage in clinical reasoning during follow‐up assessments of swallowing function, how they assess the appropriateness of initial management recommendations and how this relates to patient outcomes. What this paper adds to the existing knowledge: Our longitudinal evaluation of clinical reasoning and decision‐making patterns related to swallowing management in acute care demonstrated that SLTs tailored their processes to each patient's presentation. There was an emphasis on monitoring the suitability of the initial management recommendations and the potential for upgrade of diet or compensatory swallowing strategies. The iterative cycles of inductive and deductive reasoning reflect efficient decision‐making processes that maintain high‐quality clinical care within the acute environment. What are the potential or actual clinical implications of this work?: Employing efficient and high‐quality clinical reasoning is a hallmark of good dysphagia practice in maximizing positive patient outcomes. Developing approaches to understanding and making explicit clinical reasoning processes of experienced clinicians may assist SLTs of all developmental stages to provide high standards of care.